Diagnostic difficulties in a case of a female patient with pemphigus vulgaris - Weryńska-Kalemba, Maria; Filipowska-Grońska, Agata; Zawadzińska-Halat, Kamila; Filipowska, Karolina; Jarząb, Jerzy (Dermatology Review/Przegląd Dermatologiczny, 2016)
Introduction . Autoimmune blistering diseases are mediated by autoantibodies directed against structural proteins of the skin. Pemphigus vulgaris (PV) is the most common type of pemphigus. The main auto-antigen in PV is desmoglein 3, although other antigens such as desmoglein 1, desmocollins, plakoglobin and pemphaxin may also be involved. More than 50% of cases begin with oral lesions. Skin lesions on the face appear occasionally. Objective. To present an unusual clinical manifestation of pemphigus vulgaris. Case report . We present a case of a 54-year-old female patient with skin lesions localized on the nose, who due to suspicion of skin cancer not confirmed by histopathology was referred to us by an oncologist. Pemphigus vulgaris was suspected when erosions on the oral mucosa were observed, and this diagnosis was established on the basis of immunological tests. The patient was treated with prednisone and azathioprine, with very good results. Conclusions . We present the case owing to the difficulties in the diagnostic process and, moreover, due to spectacular clinical improvement after the treatment.